2013
DOI: 10.1074/jbc.m112.417337
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Ubiquitin Conjugation in Entamoeba histolytica

Abstract: Background: Ubiquitination plays critical roles in many cellular processes. Results: The Entamoeba histolytica ubiquitin activating, conjugating, and ligating enzymes interact and transfer ubiquitin. Conclusion: E. histolytica possesses a functional ubiquitination cascade with key differences from mammalian homologs. Significance: The E. histolytica ubiquitin-proteasome pathway may provide therapeutic targets for amoebic colitis and amoebiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The BP found as the most significant were the cellular protein catabolic process (GO:0044257), proteolysis involved in cellular protein catabolic process (GO:0051603) and protein catabolic process (GO:0030163) all with 4 fold enrichment. SUMO is the Small Ubiquitin-related Modifier protein that is important for gene transcription regulation 35 . SUMO modifies many proteins including promoter-specific transcription factors, cofactors and chromatin-modifying enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The BP found as the most significant were the cellular protein catabolic process (GO:0044257), proteolysis involved in cellular protein catabolic process (GO:0051603) and protein catabolic process (GO:0030163) all with 4 fold enrichment. SUMO is the Small Ubiquitin-related Modifier protein that is important for gene transcription regulation 35 . SUMO modifies many proteins including promoter-specific transcription factors, cofactors and chromatin-modifying enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that EhMLBP is a bi-functional protein that has a protective role in the parasite's response to heat shock by reducing the accumulation of aggregated proteins (Katz et al, 2012). Wostmann and colleagues (Wostmann et al, 1996) were the first to describe the existence a functional ubiquitin activation and conjugation pathway in E. histolytica, and its existence was later confirmed by Bosch and Siderovski (2013). In this report, we describe an interaction between EhMLBP and polyubiquitinated proteins in cytoplasmic granules that are formed in heat-shocked E. histolytica trophozoites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the increase in the MW of the EhTRF-like I and III proteins could be explained by means of this PTM that suggest a similar role. Interestingly, all the enzymes involved in SUMOylation have been identified in E. histolytica (Bosch and Siderovski, 2013 ). This allows us to propose that EhTRF-like I could have similar PTMs as TRF-1 to modulate its activity and protect telomeric DNA.…”
Section: Discussionmentioning
confidence: 99%